Identification and penicillinase testing of Neisseria gonorrhoeae from primary isolation cultures on modified New York City medium. - Young, H (1978)
The fluorescent-antibody test, rapid carbohydrate utilization test (RCUT), and a test for penicillinase production were performed on the bacterial growth from primary cultures on modified New York City medium. Of 134 gonococcal infections in men, 88.8% were diagnosed by the fluorescent-antibody test and 70.9% by the RCUT after incubation for 24 h; the corresponding figures for 75 infections in women were 86.7 and 54.7%, respectively. After incubation for 48 h, 100% of infections were diagnosed by the fluorescent-antibody test, wherease 88.8% of infected males and 86.7% of females were also diagnosed by the RCUT. Primary isolation cultures on modified New York City medium proved suitable for determining the ability of strains to produce penicillinase by a modified RCUT procedure. The method of isolation and identification by using primary cultures from modified New York City medium is both rapid and economical. The rapidity of diagnosis provided by the RCUT makes this a very useful diagnostic method, particularly in laboratories lacking immunofluorescence equipment. Since the penicillinase production test forms part of a routine identification procedure, no extra culture media or subcultures are required. The rapidity of this test should make it of value in tracing contacts of patients infected with penicillinase-producing strains.